2023
DOI: 10.1021/acs.inorgchem.3c00467
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Reactivity, and Catalytic Behavior of a Keggin Polyoxometalate/Bipyridine Hybrid in the Epoxidation of Cyclooctene with H2O2

Abstract: The present study further explores the behavior of polyoxometalate-based hybrid compounds as catalysts for liquidphase cyclooctene epoxidation with H 2 O 2 . Precisely, it unveils the nature of the relevant active species derived from the hybrid based on Keggin polyoxometalate (POM) and bipyridines (bpy) of formula (2,2′-Hbpy) 3 [PW 12 O 40 ] (1). Whereas (i) it is generally accepted that the catalytic oxidation of organic substrates by H 2 O 2 involving Keggin HPAs proceeds via an oxygen transfer route from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In contrast, treating W-1 with H 2 O 2 at 60 °C changed the solution’s color from colorless to light yellow, indicating the simultaneous formation of the peroxo-tungsten complex W(O)(η 2 -O 2 ) 2 ( W-2 ) (Figure a). Single-crystal X-ray diffraction (SC-XRD) analysis of this complex showed that W-2 has a W(VI) center coordinated to two peroxo groups (O–O), one terminal oxo group (WO), and a N , N ′-chelated 4,4′-dimethoxy-2,2′-bipyridine ligand (Figure d). The WOO geometry is similar to the crystallographically characterized structure of naphthalene dioxygenase, where dioxygen binds side-on close to the mononuclear metal at the active site (1.75 A° resolution, O–O distance, 1.45 A°) . The structurally determined O–O bond lengths of 1.47(1) and 1.51(1) A° in our complex are indicative of peroxo character of the OO moieties .…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…In contrast, treating W-1 with H 2 O 2 at 60 °C changed the solution’s color from colorless to light yellow, indicating the simultaneous formation of the peroxo-tungsten complex W(O)(η 2 -O 2 ) 2 ( W-2 ) (Figure a). Single-crystal X-ray diffraction (SC-XRD) analysis of this complex showed that W-2 has a W(VI) center coordinated to two peroxo groups (O–O), one terminal oxo group (WO), and a N , N ′-chelated 4,4′-dimethoxy-2,2′-bipyridine ligand (Figure d). The WOO geometry is similar to the crystallographically characterized structure of naphthalene dioxygenase, where dioxygen binds side-on close to the mononuclear metal at the active site (1.75 A° resolution, O–O distance, 1.45 A°) . The structurally determined O–O bond lengths of 1.47(1) and 1.51(1) A° in our complex are indicative of peroxo character of the OO moieties .…”
Section: Resultsmentioning
confidence: 71%
“…Subsequently, Liu, Engle, and their co-workers showed that a specific amino-directing group could guide a tungsten catalyst to achieve selective carbonylative functionalization of terminal alkenes at a predetermined internal position . In the context of high-valent tungsten, its use in petroleum upgrading processes and catalytic transformations, involving tungsten (+6) in a constant oxidation state for alkene , and alkyne metathesis, polymerization reactions, and epoxidation reactions, is particularly notable (Figure a). Despite significant advances, expanding the scope of applications for W(VI) beyond these areas and achieving controllable selectivity for challenging transformations not only represent meaningful chemical innovation but also enhance its organometallic characteristics. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations